The Interaction between GSTT1, GSTM1, and GSTP1 Ile105Val Gene Polymorphisms and Environmental Risk Factors in Premalignant Gastric Lesions Risk. (15th January 2017) - Negovan, Anca; Iancu, Mihaela; Moldovan, Valeriu; Mocan, Simona; Banescu, Claudia
Abstract : The study investigated the possible influence of GSTM1, GSTT1, and GSTP1 gene polymorphisms as predisposing factors for premalignant gastric lesions as well as their interaction with H. pylori infection, gastrotoxic drugs, smoking, and alcohol consumption. In this study, 270 patients with a complet set of gastric biopsies and successfully genotyped were finally included. The GSTM1 gene polymorphism had significant contribution in mild/severe endoscopic lesions (p = 0.01 ) as well as in premalignant lesions (p = 0.01 ). The GSTM1 null genotype increased the risk for mucosal defects in H. pylori -negative patients (OR = 2.27, 95% CI: 1.20–4.37) and the risk for premalignant lesions in patients with no alcohol consumption (OR = 2.13, 95% CI: 1.19–3.83). The GSTT1 deleted polymorphism did not significantly increase the risk for premalignant lesions in the absence of gastrotoxic drugs (OR = 1.82, 95% CI: 0.72–4.74). The combined GSTT1T1 and GSTM1 null polymorphisms were borderline correlated with an increased risk for premalignant lesions (OR = 1.72, 95% CI: 1.00–2.97). The wild-type GSTP1 Ile/Ile genotype versus the variant genotypes Ile/Val + Val/Val was significantly associated with a decreased risk of gastric atrophy/intestinal metaplasia (OR = 0.60, 95% CI: 0.37–0.98). In conclusion, the GSTM1 and GSTT1 null genotypes increased the risk for premalignant and endoscopic gastric lesions, modulated by H. pylori, alcohol, or gastrotoxic drug consumption, while the presence of the GSTP1Val allele seemed to reduce the risk for premalignant lesions.